2006
DOI: 10.1097/01.brs.0000244589.13674.11
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Fusion Outcomes in Washington State Workers’ Compensation

Abstract: Use of intervertebral fusion devices rose rapidly after their introduction in 1996. This increased use was associated with an increased complication risk without improving disability or reoperation rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(54 citation statements)
references
References 56 publications
5
47
0
2
Order By: Relevance
“…18 Lumbar cage fusion rates increased from 3.6% in 1996 to 58% in 2001, and the result was increased complication risk without improved disability or reoperation rates. 19 Adjacent segment degenerative changes and instability at the level immediately above single-segment fusion with clinical deterioration are shown in up to 90% of the cases. [20][21][22][23] The incidence of radiographic adjacent segment disease following fusion has been reported to be as high as 50% in the cervical spine and 70% in the lumbar spine at 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…18 Lumbar cage fusion rates increased from 3.6% in 1996 to 58% in 2001, and the result was increased complication risk without improved disability or reoperation rates. 19 Adjacent segment degenerative changes and instability at the level immediately above single-segment fusion with clinical deterioration are shown in up to 90% of the cases. [20][21][22][23] The incidence of radiographic adjacent segment disease following fusion has been reported to be as high as 50% in the cervical spine and 70% in the lumbar spine at 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…A large population-based study of fusions within the Washington State WC setting revealed a 22% re-operation rate and a low return-to-work rate of 36%, at 2-years post-surgery. 7 A more recent study in the Ohio WC jurisdiction showed similar results, with a 26% return to work rate and a 27% re-operation rate, as well as a opioid dependence disorder (ODD) still noted in 85% of fusion patients 2 years postoperative. 6 Outcomes in the Utah WC jurisdiction were comparable.…”
Section: Introductionmentioning
confidence: 75%
“…This finding provided contrast to much lower work status outcomes in prior WC spine surgery publications. [6][7][8] In addition, there were no differences in rates of additional surgery (1.2-3.7%) or new compensable injuries. These non-significant differences among groups may hide the fact that the additional surgery rates for the surgical groups ranged from 3.3-3.7%, well below fusion reoperation rates of 22-27% in recent lumbar fusion WC claim studies.…”
Section: Pre-and Post-rehabilitation Psychosocial Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Essa modalidade de tratamento apresenta como vantagens a eliminação do movimento do segmento afetado, que pode ser uma das causas da dor, e a possibilidade de uma descompressão ampla das estruturas acometidas. 14,15 O enxerto ósseo para fusão da coluna pode ser obtido de fontes locais como facetas, lâminas e processo espinhoso, do ilíaco ou ainda de banco de osso (aloenxerto). A instrumentação da coluna lombar no procedimento de artrodese é utilizada para aumentar a taxa de fusão, diminuir o tempo de imobilização e, com isso, melhorar os resultados cirúrgicos a longo prazo.…”
Section: Resultsunclassified